The Impact of Blended Mobile Learning on EFL Students’ Vocabulary Development - Aslan, Mehmet; TÜTÜNİŞ, BİRSEN (Afyon Kocatepe Üniversitesi Eğitim Fakültesi, 2024)
The study's objective is to examine the effects of Blended Mobile Learning (BML) on the vocabulary development of EFL preparatory students and their views of BML. As a mixed method study, it was conducted with 40 preparatory students at a state university in Turkey. While the control group studied vocabulary by reading texts only in the classroom by adhering to the textbook, the experimental group, in addition to the same instruction, was taught vocabulary outside the classroom in a virtual classroom opened through the Google Classroom application. A pre-test and a post-test were administered to the students to determine the impact of BML on their vocabulary development. The results of the tests were analyzed with SPSS program and the vocabulary development of groups was compared via an independent T-test. Additionally, a structured interview was done with the students of the experimental group to determine their views of BML. Students' responses were analyzed using the MAXQDA 2020 program with the method of content analysis. This research has led to the conclusion that BML, as a teaching method, strengthens the vocabulary development of the preparatory students and motivates them to learn vocabulary.
Harmanlanmış Mobil Öğrenmenin EFL Öğrencilerinin Kelime Gelişimi Üzerindeki Etkisi
▪️ This study is part of a dissertation titled “The Impact of Blended Mobile Learning on EFL Students’ Vocabulary Development” which was presented as a poster in Isatt2023: Living and Leading in the Next Era: Connecting Teaching, Research, Citizenship and Equity in Italy in July 2023 at a conference, and the abstract was published in the proceeding book.
Keywords: Blended Learning; Vocabulary; Mobile Devices; Mobile Learning; SAMR